Colletotrichum sp.- mediated synthesis of sulphur and aluminium oxide nanoparticles and its in vitro activity against selected food-borne pathogens - Suryavanshi, Pooja (2017)
Food spoilage is a major issue globally and million of people suffer from food-borne infections. Hence, there is a need to search for novel and effective antimicrobial agents. Nanoparticles act as antimicrobial agent, which can tackle the problem of food-borne pathogens. The present study includes mycosynthesis of sulphur nanoparticles (SNPs) and aluminium oxide nanoparticles (AlNPs) from Colletotrichum sp. and their characterization by UV-Vis spectroscopy, Nanoparticles Tracking and Analysis, Zeta potential measurement, X-ray diffraction and Transmission Electron Microscopy. Essential oils (EOs) were extracted from the leaves of Eucalyptus globulus and Citrus medica. Nanofunctionalized oils were formulated by combining nanoparticles with EOs. In vitro antimicrobial activity of SNPs, AlNPs, EOs and nanofunctionalized oils was evaluated against selected food-borne pathogens such as Listeria monocytogenes, Salmonella typhi, Chromobacterium violaceum, Fusarium oxysporum and Aspergillus flavus. The antimicrobial activity of SNPs was found to be maximum against Salmonella typhi (21 mm), whereas AlNPs were highly effective against F. oxysporum (22 mm). It was found that activity of antibiotics such as tetracycline, oxytetracycline, gentamicin, fluconazole, ketoconazole, amphoterecin B and nystatin. increase in combination with nanoparticles.Nanofunctionalized oil can be used as a novel antimicrobial agent the prevention of food spoilage caused by food-borne pathogens.